2017
DOI: 10.20506/rst.36.3.2734
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological studies on Clostridium perfringens food poisoning in retail foods

Abstract: Clostridium perfringens is an important anaerobic pathogen causing food-borne gastrointestinal (GI) diseases in humans and animals. Meat and meat products are the most common vehicles of C. perfringens type A food poisoning. Contamination of meat by the intestinal contents of slaughtered animals may serve as an important source of this pathogen to the food supply. One hundred and fifty-five non-outbreak food samples were obtained from meat and retail food and examined for the presence of C. perfringens. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 9 publications
2
18
1
Order By: Relevance
“…Surprisingly, our study showed that none of the 5 C. perfringens deriving from contaminated food presented the cpe gene in contrast to that reported in the literature [ 7 , 8 ]. Rosignoli et al [ 39 , 40 ] reported a unique sample food typed A but associated with the cons variant, whereas all our C. perfringens isolates were associated with the aty allelic variant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, our study showed that none of the 5 C. perfringens deriving from contaminated food presented the cpe gene in contrast to that reported in the literature [ 7 , 8 ]. Rosignoli et al [ 39 , 40 ] reported a unique sample food typed A but associated with the cons variant, whereas all our C. perfringens isolates were associated with the aty allelic variant.…”
Section: Discussioncontrasting
confidence: 99%
“…The new toxinotype F represents the formerly known CPE-positive strains of C. perfringens type A and encodes the CPA and CPE toxins upon sporulation. In this case, CPE is a typing toxin because its association with the cpa toxin genes has been demonstrated to be responsible for enterotoxigenic infections in humans [ 7 , 8 ] and animals [ 9 ]. The new type G produces the CPA toxin and the NetB toxin and is responsible for necrotic enteritis in poultry [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This means that type F C. perfringens is more often detected from infection sources such as foods and/or environments. The isolation rate of type F C. perfringens vegetative cells and spores from investigated foods, principally meat products (0–5%) [ 11 , 14 , 15 , 16 , 46 , 47 , 48 ], was lower than that of Salmonella (8–10%), EHEC (16.6%), and Campylobacter (21–27%) from foods [ 49 , 50 , 51 , 52 ]. However, the actual infection risks of type F C. perfringens infection from foods would be higher since most of these contaminated foods are heated well before eating them, so bacteria in foods would be killed excluding type F C. perfringens spores, which are heat resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to avoid the production of neurotoxin, it is essential to prevent its germination. The toxin types are classified as A, B, C, D, E, F and G. Human botulism has been mainly described with the strains of C. botulinum that produce toxin types A, B and E. Botulism outbreaks caused by different home-prepared or preserved foods have been widely reported in the literature, most of them due to improperly pasteurized or packed home-canned vegetables [3,4]; home-made oil condiments and sauces [5][6][7]; fishery products [8,9]; cheese [10,11]; or meat products [12,13]. Although it is not usual, several outbreaks in table olives have also been reported to be mainly associated with black table olives [14].…”
Section: Introductionmentioning
confidence: 99%